Phenology of wood formation and its genetic variability in larch : a step towards a better understanding of wood formation in relation to climate - Gauchat, Maria Elena (2011)
Tesis para optar al grado de Doctor, Spécialité: Sciences Forestieres et du Bois, del L'Institut des Sci ences et Industries du Vivant et de l'Environnement (AgroParisTech)-ENGREF, en 2011